Called and Chosen: Toward a Spirituality for Lay Leaders - Seton Hall University; Bechtle, Regina (Rowman & Littlefield Publishers, 2005)
That lay women and men increasingly serve as leaders of institutional ministries in the Church is nothing new. Yet, until now, these lay leaders have longed for theological resources and formational training to help them in their vocation and ministry. Called and Chosen: Toward a Spirituality for Lay Leaders is designed especially for women and men who, in collaboration with vowed religious and the ordained, shepherd Church ministries and touch the lives of countless people. Written by leading authorities in biblical studies, theology, spirituality, church history, and ecclesial leadership, the book is broken into four parts: Part one invites lay leaders to claim their own call and commitment by reflecting on the Catholic vision of spirituality, vocation, mission and ministry, and the experiences of other leaders. Part two grounds their work in the larger story of our institutional ministries by examining their biblical, theological, and historical roots. Part three probes the work of the Spirit in communities and institutions, against the backdrop of contemporary cultural realities, to help leaders develop the capacity to discern the Spirit's workings. Part four focuses on issues central to the role of a spiritual leader: the spirituality of administration, the task of building community, the use of power and authority and work of forming and mentoring others. Questions at the end of each chapter invite further reflection on the themes explored.